TOLERANSI ANTAR UMAT BERAGAMA DI SEKOLAH: Studi di SMAN 8 Singkawang Selatan Tahun pelajaran 2019/2020 - resta agustin; Rizki Susanto (IAIN Pontianak, 2020)
Abstract: Indonesia is a pluralistic country consisting of many ethnicities, religions, races and intergroups, abbreviated as SARA. The issue of SARA is interesting to discuss because SARA can be the uniqueness of an area or become a disaster if it is not regulated properly. On this occasion, the author focused on the discussion about the implementation of interfaith tolerance at SMA Negeri 8 Singkawang. This school is a multi-religious school, with 80 Muslim students, 73 Christian students, and 96 Catholic students with a total of 249 students for the 2019-2020 school year. The results showed that tolerance between religious communities in schools is an important thing, especially for public schools where students are multi-religious and there are many forms of interfaith tolerance implementation as part of the commitment to maintaining national unity and integrity. Keywords: Tolerance, Religious People, SMAN 8 Singkawang.